Strategies for Shariah Financial Literacy among Teachers: A Mental Accounting Approach - R. Suryanti Ismail; Marissa Silooy; Yosmina T.Titaley (Institut Teknologi dan Bisnis Asia Malang, 2026)
Purpose: This research aims to optimize sharia financial literacy among Muslim teachers at the Al-Hilaal Foundation, Ambon City, using a mental accounting approach. The study addresses the lack of understanding of Islamic financial principles and rational financial management among educators, who serve as vital agents of change in society Method: The study utilized a